WORK-LIFE BALANCE, ENTREPRENEURIAL STRESS, AND WORK MOTIVATION ON SMALL BUSINESS OWNERS - Parwita, Gde Bayu Surya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the relationship between work-life balance, entrepreneurial stress, and work motivation among small business owners. Utilizing a quantitative research design, data were collected from small business entrepreneurs using a structured questionnaire and analyzed through Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that work-life balance has a significant negative effect on entrepreneurial stress and a positive effect on work motivation. Additionally, entrepreneurial stress negatively impacts work motivation and partially mediates the relationship between work-life balance and motivation. These results underscore the critical role of psychological well-being in sustaining motivation and business performance. The study highlights the need for small business owners to manage their work and personal responsibilities effectively to reduce stress and maintain long-term motivational engagement. Practical implications suggest that both policy-makers and entrepreneurs should prioritize stress management and balance strategies to promote entrepreneurial sustainability.